Wireless Monitoring of Downhole Pressure Based on Tubing Transmission. (6th February 2023) - Zheng, Jian; Yang, Yang; Tan, Ting; Chen, Man; Gao, Shangjun
Abstract : Downhole pressure is an important parameter for evaluating the production status of production wells. A wireless monitoring system was designed for downhole pressure which consists of two parts, i.e., the downhole tool and the wellhead tool. The tubing was used as the information transmission medium between the two parts. The downhole tool includes four pressure sensors, and the measured results will be applied to the tubing in the form of an alternating voltage with a frequency of 2.5 Hz. The amplitude of the alternating voltage output by the downhole tool is related to the magnitude of the downhole pressure. The wellhead tool measures and decodes the signal uploaded through the tubing, and the decoded result will be transmitted to the host computer through the ground cable. The wireless transmission model of downhole pressure in the production well was equivalent to a resistance network. Simulation analysis indicates that the amplitude of the signal received by the wellhead tool is negatively correlated with the downhole depth of the downhole tool and positively correlated with the formation resistivity. The designed wireless monitoring system for downhole pressure was tested in gas-producing wells in southwestern China. The test results verified the stability and reliability of the system for downhole pressure monitoring. It also confirmed that the strength of the received signal at the wellhead is negatively correlated with the downhole depth of the downhole tool for the first time and is not affected by the structure of the wellbore. The wireless monitoring scheme of downhole pressure introduced in this paper can be extended and applied to the monitoring of other downhole parameters such as temperature.